2015
DOI: 10.1159/000380940
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Middle Ear Anomalies: Anatomical and Functional Results of Surgery

Abstract: The aim of this study was to describe the audiometric results following surgery in a consecutive series of pediatric patients with a congenital middle ear disorder. Retrospective chart review was performed for 29 consecutive children who underwent 33 middle ear surgeries for congenital ossicular chain anomaly between 1990 and 2012. Anomalies were classified into four groups according to the Teunissen and Cremers classification. Audiological parameters using four frequency averages (0.5, 1, 2 and 4 kHz) were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 14 publications
4
20
0
1
Order By: Relevance
“…Several studies reported achieving significant hearing gains by exploratory tympanotomy and ossiculoplasty in subjects with congenital ossicular anomalies [11,19,22,23]. The rate of successful ABG closure (<20 dB HL) achieved at 6 months postoperation in our study following exploratory tympanotomy and ossiculoplasty, i.e., 87.5%, is comparable to that of previous studies, which reported closure rates ranging from 56% to 70% [11,19,22,23].…”
Section: Postoperative Audiometric Outcomes In Subjects With Second Psupporting
confidence: 83%
See 2 more Smart Citations
“…Several studies reported achieving significant hearing gains by exploratory tympanotomy and ossiculoplasty in subjects with congenital ossicular anomalies [11,19,22,23]. The rate of successful ABG closure (<20 dB HL) achieved at 6 months postoperation in our study following exploratory tympanotomy and ossiculoplasty, i.e., 87.5%, is comparable to that of previous studies, which reported closure rates ranging from 56% to 70% [11,19,22,23].…”
Section: Postoperative Audiometric Outcomes In Subjects With Second Psupporting
confidence: 83%
“…Furthermore, significant improvements were observed in the AC-PTA, BC-PTA, and ABG 6 months after surgery (23.8 ± 13.2, 12.5 ± 9.4, and 11.3 ± 8.9 dB HL, respectively; p < 0.05; Figure 2). In total, 21 (87.5%) patients had achieved successful ABG closure (<20 dB HL) [19] at 6 months after surgery. Subjects with congenital ossicular anomalies who have undergone ossiculoplasty are routinely followed up until 12 months postoperation at our institution, but only 11 of 24 patients (45.8%) in the current case series were followed up until 12 months postoperation, probably due to subjective satisfaction and no further need to revisit the outpatients' clinic after 6 months postoperation.…”
Section: Postoperative Hearing Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Further comparison was made between these cases and those of ossicular malformation without CCs. Since Teunissen and Cremers [20] had published a large case series of 144 congenital ossicular anomalies in the early 1990s, a few subsequent studies provided dozens of additional cases to allow for a better understanding of this congenital defect [2,[21][22][23][24]. Based on the literature, the most common ossicular anomalies of discontinuity were absent or underdeveloped long process of the incus and the superstructure of the stapes.…”
Section: Discussionmentioning
confidence: 99%
“…It may occur independently or jointly with other ear anomalies, such as those of the outer ear and/or the inner ear [1]. The incidence of congenital ossicular anomalies is estimated at 1 in 10,000-20,000 newborns, and most cases are unilateral [2,3].…”
Section: Introductionmentioning
confidence: 99%